1992
DOI: 10.1046/j.1537-2995.1992.32993110750.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased detection of hepatitis C virus (HCV)‐infected blood donors by a multiple‐antigen HCV enzyme immunoassay

Abstract: A new, multiple-antigen enzyme immunoassay (EIA-2) for hepatitis C virus (HCV) antibodies was evaluated in parallel with the previously available c100-3 HCV EIA (EIA-1) in 14,068 volunteer blood donors as well as in 25 cases of transfusion-associated hepatitis C for which recipient and donor samples were available. When compared to EIA-1, the EIA-2 was more sensitive in detecting HCV-infected blood donors. The EIA-2 detected an additional 1 in 1000 EIA-1-negative, surrogate marker-negative donors who were infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
2
3

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(81 citation statements)
references
References 13 publications
0
75
2
3
Order By: Relevance
“…This proportion is greater than the 36% of RIBA-2 positive cases reported in similar individuals in studies conducted in Italy 16,19 and France 22 and the 39% observed in the USA 13 . In Spain, 33-63% of anti-HCV positive donors were also RIBA-2 positive 17,20 .…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This proportion is greater than the 36% of RIBA-2 positive cases reported in similar individuals in studies conducted in Italy 16,19 and France 22 and the 39% observed in the USA 13 . In Spain, 33-63% of anti-HCV positive donors were also RIBA-2 positive 17,20 .…”
Section: Discussioncontrasting
confidence: 53%
“…Of the anti-HCV donors tested, 75% were HCV RNA positive. In Italy, in the USA and in Spain the frequency of HCV RNA positivity was 66%, 58% and 63%, respectively, among RIBA-2 positive and indeterminate donors 13,16,20 . In a recent compilation 15 62% of RIBA-2 positive or indeterminate donors were HCV RNA positive, a frequency slightly lower than that observed here among our donors (75%) with an EIA ratio>3 and high positivity for RIBA-2.…”
Section: Discussionmentioning
confidence: 95%
“…The frequency of patient sepsis attributable to transfusion of bacterially contaminated blood components appears to be very low but is similar to or less than that of transfusion-associated hepatitis C virus infection, which is transmitted in approximately 1 of 2,000 to 6,000 tested units (79) …”
Section: Resultsmentioning
confidence: 96%
“…13,14 A more sensitive second-generation test became available in 1992. 15 Some transfusion-associated HCV infections continue to occur because assays currently available (secondgeneration) do not detect anti-HCV in ϳ5% of infected persons, and rare donations of blood are made by persons during the period between acquisition of infection and seroconversion. Hemodialysis patients and health care workers also are at risk as a result of exposure to infectious blood.…”
Section: Exposure To Blood and Blood Productsmentioning
confidence: 99%